New geographic and host records for scelionid wasps (Hymenoptera: Scelionidae) parasitoids of insect pests in South America - Margaría, Cecilia B.; Loiácono, Marta S.; Lanteri, Analía A. (Zootaxa, 2009)
This contribution provides new parasitoid/host associations for scelionid species distributed in Argentina, Brazil, Colombia and Uruguay, and new geographic records. The parasitoid species examined belong to the genera Gryon Haliday, Phanuropsis Girault, Trissolcus Ashmead, and Telenomus Haliday, and all of them attack insect pests. Three cases of multiple scelionid species emerging from a single egg mass of Pentatomidae are reported.